The Impact of Dipolar Layers on the Electronic Properties of Organic/Inorganic Hybrid Interfaces. Issue 14 (26th June 2019) - Zojer, Egbert; Taucher, Thomas C.; Hofmann, Oliver T.
Abstract: The presence of dipolar layers determines the functionality of most technologically relevant interfaces. The present contribution reviews how periodic dipole assemblies modify the properties of such interfaces through so‐called collective electrostatic effects. They impact the ionization energies and electron affinities of thin films, change the work function of metallic and semiconducting substrates, and determine the alignment of electronic states at interfaces. Dipolar layers originate either from the assembly of polar molecules or they arise from interfacial charge rearrangements triggered by the deposition of an adsorbate layer. Such charge rearrangements result from the omnipresent Pauli pushback caused by exchange interaction, from covalent bonds, or from charge transfer following the deposition of particularly electron rich (donors) or electron poor molecules (acceptors). A peculiarity of charge‐transfer interfaces is that they enter the realm of Fermi‐level pinning, where the sample work function becomes independent of the substrate and is solely determined by the electronic properties of the adsorbate. Beyond changing work functions and injection barriers, the presence of polar layers also modifies various other physical observables, like core‐level binding energies or tunneling currents in monolayer junctions. All these aspects suggest that polar layers can also be exploited for electrostatically designing the electronic properties of materials. Abstract : Polar layers crucially impact the electronic properties of interfaces. In this article, their fundamental properties are reviewed, their physical origin is discussed and their impact on interfacial level alignment at metal/organic and semiconductor/organic interfaces is described. Emphasis is put on how they impact physical observables like work functions, core‐level energies, and transport properties and how they could be used for electrostatically designing materials.